Different population-level vaccination effectiveness for HPV types 16, 18, 6 and 11. Issue 1 (5th October 2010) - Brisson, Marc; Van de Velde, Nicolas; Boily, Marie-Claude
Abstract : Background: Given that the human papillomavirus (HPV) vaccine types have different durations of infectiousness and infectivity, the population-level vaccine effectiveness of these types may differ even if vaccine efficacy is identical. Objective: To compare the type-specific effectiveness of vaccination against HPV types 16, 18, 6 and 11. Methods: An individual-based stochastic model of HPV transmission (18 HPV-types) in a population stratified by age, gender and sexual activity was developed. Multiple parameter sets were identified by fitting the model to sexual behaviour data and age- and type-specific HPV prevalence. Results: Under base case assumptions (70% coverage, 99% vaccine efficacy per act and 20 years' duration of protection), vaccinating 12-year-old girls is predicted to reduce HPV-16, HPV-18 and HPV-6/11 prevalence by 61% (80% uncertainty interval (UI) 53–77), 92% (80% UI 65–100) and 100% (80% UI 97–100), respectively, 50 years after the start of the vaccination programme. Differences in type-specific vaccine effectiveness increased over time, and decreased with improved vaccine efficacy characteristics. Conclusions: For the same vaccine efficacy, the population-level impact of HPV vaccination will most likely be different, with HPV-16, the most oncogenic type, having the lowest effectiveness. These results should be taken into account when designing and interpreting post-vaccination surveillance studies.